No loose ends [videorecording (DVD)] - Lockett, Darius; Lomax, Terrence, Sr; Simmons, Piffany (CM Films, 2024)
Two lifelong friends Clyde and Judas embarked on a heist that ignited a tale of ambition, loyalty, and betrayal. In debt and desperate for redemption, they go on a street style gang mission that will alter their friendship forever.